2017
DOI: 10.1186/s12917-017-1286-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of DEA 1 antigen in 1037 mongrel and PUREBREED dogs in ITALY

Abstract: BackgroundThe prevalence of dog erythrocyte antigen (DEA 1) in canine population is approximately 40–60%. Often data are limited to a small number of breeds and/or dogs. The aims of this study were to evaluate frequency of DEA 1 in a large population of purebred and mongrel dogs including Italian native breeds and to recognize a possible association between DEA 1 and breed, sex, and genetic and phenotypical/functional classifications of breeds. Frequencies of DEA 1 blood group collected from screened/enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 32 publications
9
25
1
Order By: Relevance
“…Our study also identified Dal negative dogs in the Cane Corso breed. This finding is of particular interest because the Cane Corso dog is an ancient Italian large breed dog that makes a very good blood donor for a number of reasons: large size (> 25 kg bodyweight), good temperament, easy and readily accessible jugular veins and significant higher DEA 1 and DEA 7 negative prevalence than most of the canine populations previously surveyed [7,9,11]. Our study also confirms the high prevalence of DEA 1 and DEA 7 negative subjects in this breed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study also identified Dal negative dogs in the Cane Corso breed. This finding is of particular interest because the Cane Corso dog is an ancient Italian large breed dog that makes a very good blood donor for a number of reasons: large size (> 25 kg bodyweight), good temperament, easy and readily accessible jugular veins and significant higher DEA 1 and DEA 7 negative prevalence than most of the canine populations previously surveyed [7,9,11]. Our study also confirms the high prevalence of DEA 1 and DEA 7 negative subjects in this breed.…”
Section: Discussionsupporting
confidence: 79%
“…The DEA 1 is the most studied antigen. Worldwide prevalence of DEA 1 positive dogs has been estimated to be around 50-65% [5][6][7][8][9]. DEA 1 blood type is the most clinically important blood group in terms of transfusion reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 40.8 % of all dogs in our survey were DEA 1-, which is very similar to recent surveys from USA, France, India, and Italy that also utilized the same immunochromatographic method and monoclonal anti-DEA 1 alloantibody (25,27,31,37,40).…”
Section: Dea 1 Typingsupporting
confidence: 87%
“…Boxers and Cane Corso from various other European countries and South Africa were also mostly DEA 1-in prior surveys (details in Supplement Table 4). Thus, these breeds may be preferentially considered when recruiting blood donors to increase the DEA 1-donor pool, as suggested previously (25,42) In contrast, the Dalmatians and Pugs in our survey were all DEA 1+, except for one Dalmatian. Also, the Labrador Retriever and Shih Tzu breeds had mostly DEA 1+ dogs.…”
Section: Dea 1 Typingsupporting
confidence: 66%
See 1 more Smart Citation